2020
DOI: 10.17582/journal.aavs/2020/8.2.124.129
|View full text |Cite
|
Sign up to set email alerts
|

Mycological Identification of Some Fungi Isolated from Meat Products and Spices with Molecular Identification of Some Penicillium Isolates

Abstract: M eat products are the most palatable of highly nutritive value foods for human being as they are important sources for protein, fat, essential amino acids, minerals, vitamins and other nutrients (Biesalski, 2005). On the other hand, they are considered as an ideal culture medium for growth of many organisms because of the high moisture, the high percentage of nitrogenous compounds, plentiful supply of minerals, some fermentable carbohydrates (glycogen) and of a favorable pH for most microorganisms (Alahakoon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
(8 reference statements)
1
4
0
Order By: Relevance
“…The mould species isolated from luncheon, beef burger, sausage, and minced meat were in agreement with those reported in previous studies (19,22,23,(26)(27)(28)(29)(30). The contamination of meat products with several mould genera could be due to several steps occur during meat manufacture including grinding, mincing, cooking, cooling, and packaging.…”
Section: Discussionsupporting
confidence: 91%
“…The mould species isolated from luncheon, beef burger, sausage, and minced meat were in agreement with those reported in previous studies (19,22,23,(26)(27)(28)(29)(30). The contamination of meat products with several mould genera could be due to several steps occur during meat manufacture including grinding, mincing, cooking, cooling, and packaging.…”
Section: Discussionsupporting
confidence: 91%
“…Unfortunately, certain spices are very susceptible to toxigenic microfungi growth and thus potential mycotoxin development [ 3 , 6 , 7 , 8 ]. It is known that “spices” are generally more susceptible to contamination than “herbs” [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings are similar to those of a previous report [ 28 ] that identified Aspergillus and Penicillium as the most common molds in retail meats from Alexandria, Egypt. Other studies have reported that Aspergillus species were the most common isolates from meat and environmental samples [ 29 , 30 ]. The environmental fungi Aspergillus and Penicillium are frequently used in food fermentation.…”
Section: Discussionmentioning
confidence: 99%